Effects of Tillage Disturbance on Slope Shape and Micro-topographic Features on Typical Sloping Cropland of Southwestern Alpine-canyon Area - WANG Jiaqi; WANG Yong; ZHANG Zehong; ZHANG Yixiong; LIU Jingyi; MA Zhenzhen; XIN Wang; QIN Wei; XU Haichao (Shuitu Baochi Xuebao)
[Objective] The objective of this study was to investigate the effects of various tillage practices on on slope shape and micro-topographic features on typical sloping croplands of southwestern alpine-canyon area. [Methods] 50 times of conventional tillage and contour tillage events were applied to rectangular plots (5 m×20 m) with a slope of 15° to examine the impacts of tillage disturbance on the slope shape and micro-topographic features by combining the stylus method and 3 D laser scanning technology. [Results] After 50 times of conventional tillage, the slope shape gradually evolved from a linear slope to a ‘’-type composite slope, while after contour tillage, the slope shape evolved to a ‘’-type. After 50 times of successive tillage, the range of soil loss under conventional tillage and contour tillage accounted for 15% and 11% of that of the whole slope, and the range of accumulated soil accounted for 13% and 6% of that of the whole slope, respectively. The two kinds of tillage disturbance patterns caused significant changes in the surface roughness and topographic undulation on the slope, and the degree of change of conventional tillage was greater than that of contour tillage. The average thickness of the soil loss under conventional tillage and contour tillage were 1.17 and 0.45 cm/time, respectively. Tillage frequency had the largest indirect effect on soil loss, while the disturbance patterns had the largest indirect effect on soil loss. [Conclusion] Tillage frequency and tillage pattern are the most important factors affecting slope shape and micro-topographic features. As the frequency of tillage increases, the amount of soil loss will gradually increase.